Health Literacy, Diet, and Lifestyles for the Promotion of Health and Empowerment of University Students and Staff: The “ALFADIET” Study (Epidemiology, Biostatistics, and Public Health, 2025)
IntroductionAppropriate nutrition and healthy lifestyles are key elements in the prevention of non-communicable diseases and in promoting individual well-being. In this context, health and digital literacy are essential tools to foster people’s empowerment in managing their own health. Universities, as environments with a high concentration of young people and professionals, play a strategic role in health promotion. They have the opportunity to optimize the health literacy of their students and empower them to make informed decisions for themselves and their living environments [1]. Health Literacy, meaning the ability of individuals to meet the complex demands of health in a modern society, has been associated with better health decision-making and is considered a key social determinant of healthier behaviors. Moreover, in the field of nutrition, this competency affects food selection and preparation processes and, more broadly, eating habits, thus contributing to improved health and well-being of individuals [2]. For this reason, it is important to investigate Health Literacy as well as eHealth (defined as the use of information technologies in support of health and related fields) and Digital Health Literacy, all of which are increasingly important in Public Health.ObjectivesThe ALFADIET study aims to analyze eating habits, adherence to the Mediterranean Diet, lifestyles, and levels of Health and Digital Health Literacy among students, faculty, and administrative staff of the University of Catania and the University of Palermo.MethodsThe population of the “ALFADIET” study will include students, from various degree programs and academic years, as well as teaching and non-teaching staff at the University of Catania and the University of Palermo. The study is based on an innovative real-time data collection methodology using the mobile Ecological Momentary Assessment (mEMA), aimed at capturing participants' daily behaviors. A web-based survey will be designed to collect basic demographic data and additional information. The study will use an updated, specially designed version of the HEALTHY-UNICT web app, customized and developed at the University of Catania [3]. This application will allow for the administration of validated questionnaires assessing dietary habits, behavioral factors, and health literacy. The information collected will include anthropometric variables, lifestyles (including smoking and physical activity), emotions, and demographic characteristics. The survey will be conducted on a representative sample of students, teaching and non-teaching staff, through the use of an innovative mEMA application, specially developed by an interdisciplinary team to meet the specific objectives of the study.ResultsThe preliminary findings derive from a pilot study conducted on a small sample of 27 participants from the University of Catania, including students (74.1%), faculty members (18.5%), and administrative/technical staff (7.4%). The majority were female (81.5%), with a median age of 24 years. Among students, 70% were enrolled on schedule with their academic plan, and 50% lived away from their university location. A total of 92.6% of participants reported no significant medical conditions, and 88.9% did not report any food intolerances. Regarding lifestyle habits, 81.5% reported using multivitamin and multimineral supplements, 77.8% were non-smokers, and 88.9% preferred white meat (e.g., chicken, turkey, rabbit) over red meat. Most participants (63%) slept between 7 and 9 hours per night. Psychophysical issues impacting daily activities were reported as moderately difficult by 37% of respondents, very difficult by 14.8%, and extremely difficult by one participant, while 44.4% reported no difficulties. As for digital health literacy, 55.6% stated they were very capable of finding health-related information online, 51.9% felt very capable of knowing where to look for it, and 44.4% felt very capable of evaluating the quality of such information. Additionally, 48.1% reported being very capable of distinguishing between high- and low-quality health information. However, only 29.6% felt very confident using that information to make health-related decisions.ConclusionsThis pilot study provides an initial overview of dietary habits, lifestyle behaviors, and levels of health and digital health literacy among the university population, though based on a small sample. The data collected will help identify factors associated with greater adherence to the Mediterranean Diet and higher levels of health and digital health literacy, supporting the identification of target groups for future health promotion interventions. Moreover, the study serves to test the effectiveness of innovative digital tools for real-time behavioral data collection. The future evidence will serve as a foundation for developing personalized, sustainable, and replicable strategies aimed at improving health and fostering empowerment within the academic community.